Human Resource Capacity and Work Effectiveness of the Protocol and Communications Department Employees of the Buton Regency Regional Secretariat - La Ode Syaiful Islamy H; Parlindungan Toruntju; La Didi (Sean Institute, 2024)
This study aims to explain the capacity of human resources and the effectiveness of the work of employees in the protocol and communication section of the leadership of the Buton Regency Regional Secretariat. This study uses a descriptive method with a qualitative approach. Data sources are primary data and secondary data, Data collected using interview techniques, observation and documentation. Data techniques are analyzed by preparing data and organizing data, reducing data and presenting data. The results of the study indicate that the Human Resource Capacity of employees in the Protocol and Communication Section of the Leadership of the Buton Regency Regional Secretariat is quite adequate. Employees already have good experience in carrying out their duties and responsibilities, both in preparing materials, facilitating guest services, and arranging protocol procedures. Knowledge of protocol procedures can be obtained by some employees through Bimtek and public relations and protocol training organized by both the Ministry of Home Affairs of the Republic of Indonesia and private institutions. Regarding the quality of employee work, some are adequate. This can be seen from the results of work in providing protocol services for regional leaders and protocol services for Regional Guests. Regarding the quantity of work, it shows that the workload and volume of work are very large and not balanced with the number of ASN available. So that the quantity of employee work completed is less than optimal. In the sense that all activities can be completed, but some activities are not of maximum quality. In terms of time utilization, it shows that employees are able to complete tasks and work. The ability to collaborate with all parties is one of the supporting factors so that all tasks and work can be completed properly. However, discipline in time utilization is still lacking.